Brown adipose tissues mediate the metabolism of branched chain amino acids during the transitioning from hyperthyroidism to euthyroidism (TRIBUTE) - Sun, Lijuan (2022)
Both hyperthyroidism and elevated plasma branched chain amino acids (BCAA) are associated with insulin resistance. BCAA utilization and clearance relative to thyroid status changes remains unclear. We investigate amino acids changes, specifically BCAA, during the transition from hyperthyroidism to euthyroidism, and the impact of active brown adipose tissue (BAT) on the metabolic effects of BCAA. Newly diagnosed Graves' disease participants were recruited. Hyperthyroidism was treated via a titration dosing regimen of thionamide anti-thyroid drug to establish euthyroidism over 12-24 weeks. All underwent energy expenditure (EE) measurement within a chamber calorimeter, 18F-fluorodeoxyglucose (18F-FDG) positron-emission tomography/magnetic resonance (PET/MR) imaging and plasma amino acids measurement during hyperthyroidism and euthyroidism. PET BAT maximum standardized uptake value (SUVmax), SUVmean and MR supraclavicular fat fraction (FF) quantified BAT activity. Twenty-two patients completed the study. Plasma BCAA level was significantly reduced in BAT-positive but not in BAT-negative patients during the transition from hyperthyroidism to euthyroidism. Plasma valine but not leucine and isoleucine correlated positively with insulin and HOMA-IR in hyperthyroidism. Plasma valine, leucine and isoleucine correlated with insulin and HOMA-IR in euthyroidism. Plasma valine correlated with insulin and HOMA-IR in BAT-negative but not in BAT-positive participants in both hyperthyroid and euthyroid state. However, the change (i.e. decrease) in plasma valine concentration from hyperthyroid to euthyroid state was affected by BAT-status. BAT utilizes and promotes BCAA plasma clearance from hyperthyroid to euthyroid state. Active BAT can potentially reduce circulating BCAA and may help to ameliorate insulin resistance and improve metabolic health.Clinical trial registration: The trial was registered at clinicaltrials.gov as NCT03064542.